PENGARUH CITRA MEREK, KERAGAMAN PRODUK, DAN SUASANA TOKO TERHADAP LOYALITAS PELANGGAN DI TOKO KARTIKA KEBAYA BEDUGUL - Dewa Ayu Dwi Pratiwi Widianti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
Kebaya is clothing worn by women in every ceremonial activity in Bali. Kebaya began to experience changes in terms of design and materials used as a result of developments over timeThis research aims to determine the influence of brand image, product diversity and store atmosphere on customer loyalty at the Kartika Kebaya Bedugul Store. The population in this research is all consumers who have purchased at least 2 times the Kartika Kebaya Store products. The number of samples in this study was 102 people who were determined using the purposive sampling method with the formula for the number of indicators multiplied by 6. The analytical tool used to test the hypothesis was multiple linear regression. The research results show that brand image has a positive and significant effect on customer loyalty at the Kartika Kebaya Store. Product diversity has a positive and significant effect on customer loyalty at the Kartika Kebaya Store. The shop atmosphere has a positive and significant effect on customer loyalty at the Kartika Kebaya Shop. Looking at the research results, it is recommended that the Kartika Kebaya Store be able to maximize the strength of product diversity by adding new types of products and creating a good store atmosphere that suits customer tastes..